Design and Construction of Teacher and Student Attendance Using Website-Based Radio Frequency Indentification: Case Study of SDN 011 Tenggarong Seberang - Muhammad Rezha Nur Hakiki; Salmon Salmon; Ivan Haristyawan (Sebatik, 2025)
This study aims to design and develop a teacher and student attendance system using Radio Frequency Indentification (RFID) technology integrated with a web-based platform as a solution to challenges encountered in manual attendance recording at SDN 011 Tenggarong Seberang. Conventional methods often result in delayed recapitulation, data entry errors, and difficulties in presenting attendance information quickly and accurately. By utilizing RFID technology, the attendance process is automated when the card is detected by the system, allowing data to be stored directly in the database without manual input. Integration with a web-based application enables real-time access to attendance data, presentation in structured reports, and analysis according to school administrative needs. The system development involved stages of requirements analysis, system architecture design, RFID device implementation, web interface creation, and functional testing to ensure accuracy and speed of data recording. The results indicate that the digital attendance system significantly improves administrative efficiency, reduces recording errors, and supports the monitoring of teacher and student discipline. Additionally, the web-based system provides flexibility for operators to manage and review attendance records. Therefore, the implementation of an RFID-based web attendance system is proven effective in supporting the modernization of administrative management in elementary schools.